Thyroid nodules with highly suspicious ultrasonographic features, but with benign cytology on two occasions: is malignancy still possible? - Rosário,Pedro Weslley (2016)
ABSTRACT Objective There is no information about the frequency of malignancy specifically in the case of thyroid nodules with highly suspicious sonographic features, but with two fine needle aspiration (FNA) showing benign cytology. This was the objective of the study. Subjects and methods We report the results of 105 patients with thyroid nodules considered “highly suspicious” according to the ultrasonographic classification of American Thyroid Association, in whom FNA revealed benign cytology on two occasions (interval of 6 months). Results Thyroidectomy was performed in 11 cases due to desire of the patient or significant growth of the nodule. In these patients, cytology continued to be benign in 9, was non-diagnostic in 1, and suspicious in 1. Histology revealed papillary carcinoma in only one nodule. In patients in whom a third FNA was obtained for this study (n = 94), cytology continued to be benign in 86, became non-diagnostic in 5, indeterminate in 2, and suspicious in 1. The last 8 patients (with non-benign cytology) were submitted to thyroidectomy and histology revealed malignancy in only one nodule. Conclusion The rate of malignancy found here for nodules with highly suspicious sonographic features, even after two FNA showing benign cytology, was 2%. We believe that in these cases, the continuation of follow-up consisting of ultrasound at intervals of 2 years may still be adequate.